A NEW THREE -TERM CONJUGATE GRADIENT ALGORITHM FOR SOLVING MINIMIZATION PROBLEMS - Omar, Dilovan H.; Shareef , Salah G.; Fathi , Bayda G. (Science Journal of University of Zakho, 2023)
The method of optimization is used to determine the most precise value for certain functions within a certain domain; it is mostly studied and employed in the fields of mathematics, computer science, and physics. This work presents a novel three-term conjugate gradient (CG) approach for unconstrained optimization problems. Both the descending criteria and the sufficient descent criterion were met by the new approach. The novel method that has been proposed has been evaluated for global convergence. The outcomes of numerical trials on a few well-known test functions demonstrated how highly successful our new modified method is, depending on the number of iterations (NOI) and the number of functions to be evaluated (NOF).
Keywords: Optimization; Conjugate Gradient Methods; Three Terms Conjugate Gradient